Functional mapping of factor VIII C2 domain - Pellequer, Jean-Luc; Chen, Shu-wen W.; Saboulard, Didier; Delcourt, Marc; Négrier, Claude; Plantier, Jean-Luc (Thrombosis and Haemostasis, 2011)
The factor VIII (FVIII) is a cofactor of the coagulation cascade. The FVIII C2 domain is a critical domain that participates in the interactions with the von Willebrand factor and the phospholipidic surfaces. To assess the importance of each residue of this domain in the maintenance of the structure and the function of FVIII, a number (n=139) of mutants were generated by substituting the original residues, from Ser2173 to Gly2325, by an alanine. Mutants were built within a complete B domain- deleted FVIII and expressed in COS-1 cells. Mutant antigen levels and procoagulant activities were measured. Two in silico analyses, a sliding average procedure and an analysis of the mutation energy cost were conducted in parallel on the FVIII structure. Both results were in agreement with the functional data, and illustrated the benefit of using such strategies prior to targeting specific residues in the aim of generating active recombinant molecules. The functional assays identify the residues that are important to maintaining the structure of the C2 domain, mainly those forming β-sheet, and those that can afford substitution, establishing a detailed functional relation with the available crystallographic data. This study provided a comprehensive functional mapping of the FVIII C2 domain and discussed the implication of specific residues in respect to the maintenance in the activity and structure stability, the efficiency in secretion, the binding to phospholipids and the formation of epitope.
Keywords: Coagulation factors; factor VIII; protein structure / folding